Simplified Guide to MR Elastography in Early Detection of Hepatic Fibrosis with Case Reports - Amit Kharat (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
The current unhealthy diets and sedentary lifestyle have led to increase in the prevalence of diabetes and metabolic syndrome globally. Fatty liver is a common occurrence in metabolic syndrome. The liver health is often ignored due to delayed warning signs. Fatty changes of the liver is one of the common findings in ultrasonography. Ultrasound does not detect fibrosis except when cirrhosis is developed. Early stages of fibrosis are asymptomatic with no significant laboratory or preliminary imaging findings. With fibrosis, the elasticity of the liver is reduced and becomes stiffer. Over the years, many techniques have developed to assess the stiffness of the liver, starting from palpation, ultrasonography, and recently developed magnetic resonance elastography (MRE). In this article, we have tried to simplify the concepts of MRE to detect fibrosis and present few case reports. The basic steps involved in generating elastograms and interpretation with some insight on how to incorporate it into the clinical workflow are discussed. MRE is superior to various other available techniques and even offers certain advantages over biopsy. MRE is FDA approved for liver fibrosis since 2009, yet it is hardly used in the Indian setting. MRE is a safe and noninvasive technique to evaluate a large volume of the liver and can be a new norm for the evaluation of fatty liver. Magnetic resonance imaging (MRI)-based elastography techniques hold an exciting future in providing mechanical properties of tissues in various organs like spleen, brain, kidney, and heart.